LEVEL OF PUBLIC PARTICIPATION IN THE POLICY OF PREPARATION OF REGIONAL REVENUE AND EXPENDITURE BUDGET (APBD) - HERNIMAWATI, HERNIMAWATI (Human Sustainability Procedia, 2018)
The objective of this research is to reveal and analyze the phenomenon of public participation in the policy of APBDpreparation especially in Pekanbaru City.This research is developed based on qualitative research with interpretive paradigm. The approach and technique of phenomenology analysis used to explore comprehensive meaning of participation phenomenon on local government budgeting policy. The research result indicated the phenomenon of public participation on local government budgeting policy still be assumed utopis because the low of socialization to public so that only certain public of which can access information and proposes program, and when mechanism of Musrenbangkot is desisted hence compilation step of APBD hereinafter more in dominated with politics problem.